Resilient microring resonator based photonic networks - Nitta, Christopher J.; Farrens, Matthew K.; Akella, Venkatesh (MICRO 44 : Proceedings of the 44th Annual IEEE/ACM Symposium on Microarchitecture, December 4 - 7, 2011 Porto Alegre, RS - Brazil, 2011)
Microring resonator-based photonic interconnects are being considered for both on-chip and off-chip communication in order to satisfy the power and bandwidth requirements of future large scale chip multiprocessors. However, microring resonators are prone to malfunction due to fabrication errors, and they are also extremely sensitive to fluctuations in temperature. In this paper we derive a fault model for microring based optical links that can be used by computer architects to make informed design choices. We evaluate different schemes for improving resilience, such as retransmission versus error-correction, using an optical fault simulator based on our fault model. We show how meeting a target mean time between failures (MTBF) affects the choice of resilience scheme - our investigation indicates that until fault rates are in the range of 10 -21 to 10 -24 per cycle, error detection/correction schemes will be needed in order to meet a 1M hour MTBF. We also evaluate how the resilience scheme impacts the performance of the link, which will help an architect choose the appropriate scheme based on the throughput requirements of a particular design.